UPPGHA : uniform privacy preservation group handover authentication mechanism for mMTC in LTE-A networks - Cao, Jin (2020)
Machine Type Communication (MTC), as one of the most important wireless communication technologies in the future wireless communication, has become the new business growth point of mobile communication network. It is a key point to achieve seamless handovers within Evolved-Universal Terrestrial Radio Access Network (E-UTRAN) for massive MTC (mMTC) devices in order to support mobility in the Long Term Evolution-Advanced (LTE-A) networks. When mMTC devices simultaneously roam from a base station to a new base station, the current handover mechanisms suggested by the Third-Generation Partnership Project (3GPP) require several handover signaling interactions, which could cause the signaling load over the access network and the core network. Besides, several distinct handover procedures are proposed for different mobility scenarios, which will increase the system complexity. In this paper, we propose a simple and secure uniform group-based handover authentication scheme for mMTC devices based on the multisignature and aggregate message authentication code (AMAC) techniques, which is to fit in with all of the mobility scenarios in the LTE-A networks. Compared with the current 3GPP standards, our scheme can achieve a simple authentication process with robust security protection including privacy preservation and thus avoid signaling congestion. The correctness of the proposed group handover authentication protocol is formally proved in the Canetti-Krawczyk (CK) model and verified based on the AVISPA and SPAN.